Determination of performance and exhaust emissions properties of B75 in a CI engine application - Ilkilic, Cumali; Aydin, Huseyin (Elsevier Science Bv, 2011)
In this study, performance and exhaust emissions of biodiesel in a compression ignition engine was experimentally investigated. Therefore, biodiesel has been made by transesterification from cotton seed oil and then it was mixed with diesel fuel by 25% volumetrically, called here as B75 fuel. B75 fuel was tested, as alternative fuel, in a single cylinder, four strokes, and air-cooled diesel engine. The effect of B75 and diesel fuels on the engine power, engine torque and break specific fuel consumption were clarified by the performance tests. The influences of 875 fuel on CO, HC, NOx, Smoke opacity, CO(2), and O(2) emissions were investigated by emission tests. The engine torque and power, for B75 fuel, were lower than that of diesel fuel in range of 2-3%. However, for the 675, specific fuel consumption was higher than that of diesel fuel by approximately 3%. CO(2), CO, HC, smoke opacity and NO(x) emissions of B75 fuel were lower than that of diesel fuel. The experimental results showed that 875 fuel can be substituted for the diesel fuel without any modifications in diesel engines. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Alternative fuels; Biodiesel; Diesel fuel; Emission; Diesel engine